Impact of gender and mutational differences in hormone receptor expressing non-small cell lung cancer - Hsu, Robert; Chen, Denaly; Xia, Bing; Feldman, Rebecca; Cozen, Wendy; Raez, Luis E.; Borghaei, Hossein; Kim, Chul; Nagasaka, Misako; Mamdani, Hirva; Vanderwalde, Ari M.; Lopes, Gilberto; et al. (Frontiers in Oncology, 2023)
Background: The incidence of lung cancer in the US has been decreasing but a bigger decline has been observed in men despite similar declines in tobacco use between men and women. Multiple theories have been proposed, including exposure to exogenous estrogens. Our study seeks to understand the relationship between hormone receptors (HR), gender, and the genomic landscape of non-small lung cancer (NSCLC). Methods: 3,256 NSCLC tumor samples submitted for molecular profiling between 2013-2018 were retrospectively identified and assessed for HR expression. Hormone receptor positivity (HR+) was defined as >1% nuclear staining of estrogen receptor-alpha (ER-a) or progesterone receptor (PR) by immunohistochemistry. DNA sequencing by NGS included cases sequenced by the Illumina MiSeq hot spot 47 gene panel (n=2753) and Illumina NextSeq 592 gene panel (n=503). An adjusted p-value (q-value) <0.05 was determined significant. Results: HR+ was identified in 18.3% of NSCLC. HR+ occurred more commonly in women compared to men (19.6% vs 11.4%, p <0.0001, q <0.0001). EGFR mutations occurred more commonly in HR+ NSCLC than HR- NSCLC (20.2% vs. 14.6%, p = 0.002, q=0.007). Overall, men with EGFR mutations were affected by HR status with a higher prevalence in HR+ NSCLC while such differences were not seen in women. However, in women ages 45, there was a trend towards greater prevalence HR+ NSCLC (25.25% vs. 11.32%, q= 0.0942) and 10/25 (40.0%) of HR+ cases in young women were found to be EGFR mutated. KRAS mutations and ALK+ IHC expression occurred more in HR+ NSCLC whereas TP53 mutations occurred more in HR- NSCLC. Conclusions: Women were more likely to have HR+ NSCLC than men and EGFR and KRAS mutations occurred more commonly in HR+ NSCLC. Additional studies with more strict inclusion criteria for HR+ are warranted to see if there is benefit to targeting HR in these subgroups.